KEARIFAN LOKAL MASYARAKAT DALAM MENGELOLA SUMBER MATA AIR DI DESA CAONG KECAMATAN MEMPAWAH HULU KABUPATEN LANDAK - Iren, Frederikus; Zainal, Sofyan; Roslinda, Emi (JURNAL HUTAN LESTARI, 2020)
Local wisdom is the value or attitude of local people's life in interacting with the environment where they live in a wise life. The village of Caong has local wisdom in the management of water sources. This research aims to assess the local wisdom of the community in managing water sources and analyzing the relationship of social perception in applying local wisdom from each factor such as customary law, trust, and Knowledge. The method used in this research is the survey method with an interview technique with a questionnaire, and the respondents taking purposive random sampling. Analysis of data using descriptive analysis with Chi-Square test analysis and inferential analysis using the non-parametric analysis correlation of Kendall Tau. The number of respondents used in this study was 85 respondents. Local wisdom conducted by the community of Caong village in managing the source of the water, namely the activities of managing the springs and traditions and rituals of society: the activities of administering the water source (making dams (Pagunkg), and team cleaning springs, planting Trees, repair facilities, and create drains). Local wisdom in the form of community traditions and rituals on the management of the source of water, are customary law, norms, special rules, and traditional rituals of worship in the spring water (nyangahan't ka ulu ai). Public perception of water resources management tends to be positive, high customary law, high level of community confidence, and high level of community knowledge. There is a significant link between public perception on the management of the water source of Caong village with customary law, trust, and knowledge.Keywords: Caong village, local wisdom, management, water resources.